APPLICATION VEGETABLE OIL AS A COATING ON THE FREEZ SLICES CARROT (Daucus carrota) AND THE QUALITY CHANGES DURING STORAGE - Priska Wisudawaty, Sugiarto dan Chilwan Pandji (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Carrot is highly perishable commodity due to respiration. This process can decompose the macro molecule into carbon dioxide, water, and other micro molecule. This decomposing will lead to softening of tissue. This damage could be reduced by fast freezing and then stored under frozen. The research was aimed to  know the effect of freezing time and the kind of oil used as coating on color, texture, weight loss and total dissolved solids of the slice carrot during storage. The result of this study showed that oil gave significant effect on the quality of carrot. The best oil for coating was corn oil that gave weight up to 0.06%, total dissolved solid in the range 4 to 6 brix, color of 67 till 69 Hue, violence in between of 1.30 and 3.50 mm/s, and it was favored by consumers even after 54 day storage.                                                                                                                Keywords : coating, frozen carrot, oil